Le mal et la symbolique Ricœur lecteur de Freud - Thiriez-Arjangi, Azadeh; Dierckxsens, Geoffrey; Funk Deckard, Michael; Bruzzone, Andrés (De Gruyter, 2022)
This book outlines the trajectory from Paul Ricœur's The Symbolism of Evil to his writings devoted to psychoanalysis, the common thread being the residue left by the subject of evil, which guided Ricœur to Freud. This book is a collection following two Fonds Ricœur summer workshops co-organized with the Society for Ricœur Studies at the Ricœur Archive in Paris. It is a groundbreaking work for those interested in Ricœur, Freud and religion.